Carbon footprint assessment and mitigation options of dairy under Chinese conditions - Koning, Kees de; Vries, Marion de (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2018)
Presentation to the Chinese Academy of Agricultural Sciences (CAAS) 16 October 2018, Beijing, China Presented by Kees de Koning, Chairman Steering Committee Sino Dutch Dairy Development Centre, Wageningen University and Research Centre